2016
DOI: 10.1093/jamia/ocw169
|View full text |Cite
|
Sign up to set email alerts
|

Graphics help patients distinguish between urgent and non-urgent deviations in laboratory test results

Abstract: Objective: Most electronic health record systems provide laboratory test results to patients in table format. We tested whether presenting such results in visual displays (number lines) could improve understanding. Materials and Methods: We presented 1620 adults recruited from a demographically diverse Internet panel with hypothetical results from several common laboratory tests, first showing near-normal results and then more extreme values. Participants viewed results in either table format (with a "standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 33 publications
3
63
1
Order By: Relevance
“…Though there has been mention of the importance for user-centered design when developing patient-facing applications within EHRs [11] (such as patient portals), few studies have managed to carry-out the user-centered design process [12] in its entirety. The majority of studies on patient-centered design have explored patients’ information needs when interpreting their test results and how appropriate informatics tools can improve patient comprehension of health concepts [1314151617]. However, few published studies have attempted to take the next steps to use these information requirements to propose new designs for patient-facing interfaces or tools that promote patients’ comprehension of test results and to test these interfaces with patients [16].…”
Section: Background and Significancementioning
confidence: 99%
“…Though there has been mention of the importance for user-centered design when developing patient-facing applications within EHRs [11] (such as patient portals), few studies have managed to carry-out the user-centered design process [12] in its entirety. The majority of studies on patient-centered design have explored patients’ information needs when interpreting their test results and how appropriate informatics tools can improve patient comprehension of health concepts [1314151617]. However, few published studies have attempted to take the next steps to use these information requirements to propose new designs for patient-facing interfaces or tools that promote patients’ comprehension of test results and to test these interfaces with patients [16].…”
Section: Background and Significancementioning
confidence: 99%
“…Regarding benchmarks, Zikmund-Fisher et al demonstrated that visualizations of benchmark ranges for test results can help patients interpret data and distinguish near-normal from atypical results [60]. However, Wilcox et al point out that clinicians sometimes object to the presentation of reference ranges because they are not appropriate in all cases [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, thus far researchers have largely focused on data collected by patients or their family members. Although researchers have begun to explore better ways to present data provided to patients by health care organizations [22,60], much work remains to be done on how to support patient-provider collaboration in the hospital, where clinicians collect and control the bulk of patient data. Thus far, studies in this space have shown that hospitalized patients value the ability to ask their clinicians questions electronically [57], “triage” their inquiries [57], and set personalized health goals [10].…”
Section: Related Workmentioning
confidence: 99%
“…As stated above, there have been a number of proponents of more graphical formats, both in the medical literature [12,13] and in the wider public arena [14]. Proposed tools include the use of graphical outputs with colour shaded areas to indicate risk [12,13], miniature graphical tools (sparklines) [12] and tools to highlight changes within an individual in addition to as well as absolute values of results [15].…”
Section: Alternative Data Presentationsmentioning
confidence: 99%